Математическая модель переходных процессов в системах электроснабжения с двигательной нагрузкой и ее программная реализация - Веприк, Юрий Николаевич; Небера, Ольга Алексеевна; Свиридов, А. П. (Кировоградский национальный технический университет, 2016)
В статье представлена модель систем электроснабжения в переходных режимах и её программная реализация на основе уравнений в фазных координатах, которая позволяет воспроизводить как электромагнитные, так и электромеханические составляющие переходных процессов в электрической сети произвольной конфигурации.

The article presents a model of of power supply systems in transient modes based on the equations in the phase coordinates, which allows you to reproduce transients in the electrical network of any configuration. Based on the presented model have been developed software tools that allow to research of electromagnetic and electromechanical switching transients (symmetrical and asymmetrical short-circuit, automatic reclosure, supply interruptions, ARS, etc..) in electrical networks with the motor load for the choice of means of antifault control and protection. Transition to modeling based on phase coordinates allows to extend the capabilities of models, and also to take into account factors that are not considered by traditional models.
A mathematical model transients in power supply systems with motor load and its software implementation
Keywords: координаты фазные; машины электрические; уравнения дифференциальные; transients; phase coordinates; mathematical model; electrical machines; motor load